Bringing the Real World of Science to Children: A Partnership of the American Museum of Natural History and the City University of New York - Picciano, Anthony G.; Steiner, Robert V. (Online Learning, 2008)
Every child has a right to an education. In the United States, the issue is not necessarily about access to a school but access to a quality education. With strict compulsory education laws, more than 50 million students enrolled in primary and secondary schools, and billions of dollars spent annually on public and private education, American children surely have access to buildings and classrooms. However, because of a complex and competitive system of shared policymaking among national, state, and local governments, not all schools are created equal nor are equal education opportunities available for the poor, minorities, and underprivileged. One manifestation of this inequity is the lack of qualified teachers in many urban and rural schools to teach certain subjects such as science, mathematics, and technology. The purpose of this article is to describe a partnership model between two major institutions (The American Museum of Natural History and The City University of New York) and the program designed to improve the way teachers are trained and children are taught and introduced to the world of science. These two institutions have partnered on various projects over the years to expand educational opportunity especially in the teaching of science. One of the more successful projects is Seminars on Science (SoS), an online teacher education and professional development program, that connects teachers across the United States and around the world to cutting-edge research and provides them with powerful classroom resources. This article provides the institutional perspectives, the challenges and the strategies that fostered this partnership.